204 The cardiac hepcidin/ferroportin axis is essntial for cardiac iron homeostasis and function. (5th June 2017) - Lakhal-Littleton, Samira; Wolna, Magda; Chung, Yu-Jin; Christian, Helen; Heather, Lisa; Brescia, Marcella; Ball, Vicky; Diaz, Rebeca; Santos, Ana; Biggs, Daniel; Clarke, Kieran; Davies, Benjamin; et al.
Abstract : Background: Iron deficiency and chronic heart failure are two of the most common disorders worldwide. Recent evidence has demonstrated that they are linked. Moreover, clinical trials have demonstrated the benefits of intravenous iron supplementation in chronic heart failure. However, cardiac iron homeostasis remains unexplored. Recently, our laboratory demonstrated that cardiac-specific deletion of the ?iron-?exporting protein ferroportin causes fatal cardiac iron overload1. Ferroportin is known to be downregulated by the liver-derived hormone hepcidin. But hepcidin is also found in cardiomyocytes where its function remains unknown. Methods and results: To explore the function of cardiomyocyte hepcidin, we generated mice with a cardiomyocyte-specific deletion of hepcidin or with a cardiomyocyte-specific knock-in of a hepcidin-resistant ferroportin mutant. While both models maintain normal systemic iron homeostasis, they nevertheless develop cardiomyocyte metabolic dysfunction followed by fatal contractile impairment as a consequence of cardiomyocyte iron deficiency. Intravenous iron supplementation prevents both the development of metabolic dysfunction and contractile impairment. 2 Conclusions: We conclude that regulation of iron export from cardiomyocytes by the cardiac hepcidin/ferroportin axis is essential to cardiomyocyte iron homeostasis and that its disruption leads to fatal cardiac dysfunction, even against a background of intact systemic iron homeostasis. These findings raise the possibility that hepcidin agonists/antagonists developed for disorders of systemic iron homeostasis could also modulate cardiac function. References: 1. Lakhal-Littletonet al. An essential cell-autonomous role for hepcidin in cardiac iron homeostasis. Elife. 2016Nov 29;5. pii: e19804. doi: 10.7554/eLife.19804. 2. Lakhal-Littletonet al. Cardiac ferroportin regulates cellular iron homeostasis and is important for cardiac function. PNAS, 2015;112, 3164–3169.